Identifying Struggling Students: Exploring Student Factors Such as Gaming Addiction Which Lead to Grade Retention and Other Challenges (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study is part of a Capstone project developed during an immersion phase in Orange County, Florida, and explores the impact of excessive technology use, specifically gaming addiction, on student behavior and academic performance. Observations from eight years of teaching and two years of counseling in Saudi middle schools revealed that students exhibiting disruptive behaviors often had excessive engagement with electronic devices. The project employed workshops and surveys to raise awareness about video game addiction and its associated symptoms, such as depression, social isolation, and strained relationships with parents and teachers. The study incorporated qualitative and quantitative data from parents and school counselors to propose strategies aligned with Vision 2030’s goal of fostering student engagement and success. Key findings indicated the pressing need for targeted interventions to address gaming addiction among students. By leveraging insights from the immersion phase and incorporating feedback from stakeholders, the study presents innovative approaches to support Saudi students in overcoming technology-related challenges. These findings underscore the potential for sustainable educational improvements through practical and evidence-based solutions.